Inovasi Teknologi Pemasaran Terintegrasi bagi Pembudidaya Ikan Hias - Siswanto, Tito; Gusneli, Gusneli; Mardika, Isnan Hari (Journal Pemberdayaan Masyarakat Indonesia, 2022)
The main problems faced by partners in general are marketing problems; It is still limited and conventional and there is no integrated marketing between decorative fish cultivators. A solution to the main problem is the application of integrated marketing technology using joint marketing methods for decorative fish cultivators in Parigi Mekar Village, Ciseeng District. In particular, this program has the objective of increasing market reach for decorative fish cultivators through website media, and increasing sales effectiveness by creating decorative fish sales centers. The activity approach method is through a participatory approach. This approach emphasizes efforts to improve human quality in order to increase real participation in activities. Devotion provides value to farmers and creates a positive image of the partner's location as the largest ornamental fish producer in West Java through the Ornamental Fish Village brand. In addition, by implementing the program effectively and sustainably, the program can motivate cultivators to develop their cultivation results. Other support in the form of website-based digital marketing can also reach a wider market network which has an impact on creating connectedness between cultivators and outsiders.